Reverse causality between oil policy and fiscal policy? The Venezuelan experience - Osmel Manzano; José Luis Saboin (Inter-American Development Bank (IDB), 2021)
This paper uses a model of intergenerational accounting to simulate the intergenerational distribution of oil wealth in Venezuela. Venezuelan oil production does not seem to follow an optimal extraction path. Nevertheless, this is true if we do not consider what the government does with the resources received from the oil sector. In this paper we explored the interaction of oil policy and fiscal policy using an intergeneration accounting model. We found that these interactions could explain certain outcomes. In particular, the model could explain why the sector was open for investment in 1991 and then 're-nationalized' in 2001. Results suggest that when fiscal policy could leave an important burden to future generations, voters seem to favor a more tax oriented oil policy, leaving the oil in the subsoil.
Keywords: E21; E22; E24; E32; E62; E65; H13; H21; H50; L71; N16; N56; O13; P16; Q38; 330; Oil policy; Fiscal policy; Intergenerational accounting; Fiscal voracity; Oil expropriation cycles; Venezuela